Hubungan Perilaku Keluarga Sadar Gizi (Kadarzi) Dengan Status Gizi Balita Di Kampung Pelita Medika FK UNRI - Wahyuni, Sri; Fauzia, Dina; Pratiwi, Nurfi; Khairati, Syahrul (Fakultas Kedokteran Universitas Riau, 2024)
Nutrition-aware families (Kadarzi) are a government effort to reduce morbidity or mortality. One of the efforts of Kadarzi behavior is to routinely weigh children under five years (toddler) to determine their nutritional status, which is one indicator of Kadarzi behavior. This study aims to see the relationship Kadarzi behavior and the nutritional status of toddlers in Kampung Pelita Medika (KPM) FK UNRI. This study uses an analytical approach with a cross-sectional design conducted from June to November 2021. The results of this study showed that was a relationship between Kadarzi behavior and the nutritional status of toddlers based on the Weight/Age, Length (Height)/Age, and Weight/Height indices, where each p value =1.000; p = 0.001; and p = 0.000 with Prevalence Ratio (PR) value = 1.02 (0.98-1.06); PR = 10.68 (2.16-52.93); and PR=7.68 (2.39-21.53) which means that dietary behavior is a risk factor related to the nutritional status of toddlers.